(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
This article explores the art of the "woodcut", his role in the visual arts, the art of woodcuts first appeared in Mesopotamia and moved to China, Germany, and Russia. There he later subsequently entered the art of woodcut in Uzbekistan in 1970-90, actively engaged in this kind of art. Examples of creative works by artists are presented.